2010
DOI: 10.3367/ufne.0180.201003e.0289
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Ge hut clusters in arrays formed by molecular beam epitaxy at low temperatures on the Si(001) surface

Abstract: Morphological investigations and classification of Ge hut clusters forming the arrays of quantum dots on the Si(001) surface at low temperatures in the process of the ultrahigh vacuum molecular beam epitaxy have been carried out using in situ scanning tunnelling microscopy. Two main species of Ge hut clusters composing the arrays-pyramidal and wedge-shaped ones-have been found to have different atomic structures. The inference is made that shape transitions between pyramids and wedges are impossible. The nucle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
102
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(104 citation statements)
references
References 53 publications
2
102
0
Order By: Relevance
“…1,4,10,15,28 Our STM data demonstrate these two cluster forms to grow from different types of nuclei which have different structures and symmetries: 15,18 Fig. 1 presents STM images of these nuclei and models of arrangement of their atoms on WL.…”
Section: B Summary Of Main Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1,4,10,15,28 Our STM data demonstrate these two cluster forms to grow from different types of nuclei which have different structures and symmetries: 15,18 Fig. 1 presents STM images of these nuclei and models of arrangement of their atoms on WL.…”
Section: B Summary Of Main Resultsmentioning
confidence: 99%
“…Exploration of apex structure of bigger huts has shown that it is also different for pyramids and wedges. 4,15 Both nuclei reconstruct WL patch tops on which they appear (each on a single patch). Nuclei of pyramids transform to 3-D huts without any further reconstruction; a growing pyramid always reproduces a blossom-like shape of the nucleus on its vertex keeping its apex unchanged (Fig.…”
Section: B Summary Of Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations